The Effect of Information Quality and Video Clipper Popularity on Users’ Trust in Information: An Elaboration Likelihood Model Approach - Dafa Al Faris Anwar; Apriansyah Putra; Ari Wedhasmara; Rizka Dhini Kurnia (SISTEMASI, 2026)
The rapid growth of short-form video-based social media has transformed the way users consume information, enabling faster and more immediate access to digital content. One emerging phenomenon is video clipper content, which consists of short clips extracted from longer videos and presented in a concise format that may influence users' understanding of and trust in the information presented. This study aims to examine the effects of information quality and video clipper popularity on users' trust in information using the Elaboration Likelihood Model (ELM) as the theoretical framework. A quantitative research approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Data were collected through an online questionnaire from 150 respondents who had previously consumed video clipper content. The results indicate that information quality, representing the central route, does not have a significant effect on users' trust in information. In contrast, popularity, representing the peripheral route, has a positive and significant effect on users' trust in information. Collectively, the two variables explain users' trust in information with an R² value of 0.872, indicating substantial explanatory power. These findings suggest that, in the context of video clipper content consumption, users tend to base their trust more on popularity cues than on the quality of the information itself. This study highlights the importance for content creators and social media platforms to prioritize information credibility and quality in order to reduce the risk of user misunderstanding and the spread of misleading information.